(untitled) (Linguostylistic Studies, 2018)
The article elucidates the issue of creating official and informal names of the village of Zatyshshia residents (based on the novel “Blue Chamois” by M. Nesterchuk). The study has revealed the word-forming patterns with productive and unproductive suffixes in the proper name variants and classified the novel characters’ nicknames in the lexical-semantic motivational groups. The study has revealed that multifunctional formants derived from the first names dominate in the surname derivatives. We have revealed 65 anthroponyms in the novel, including 29 official proper personal male names and 12 female; 11 male and 27 female names have been recorded only in variants. There are also versions formed by compounding: Kots-Kutsky, Moschniaha-Mighty, Motsuhyria-Mochurad, Moshenets-Moschniaha-Mighty. Most surnames (12) are with multifunctional formants, ending in -uк, -chuк, there are also 5 names with suffixes -sky, -tsky, and 4 surnames on -k-o. Such names are formed in a lexico-semantic way, and are based on the calendar names of the founders or indicate to their place of residence. Among the lexical-semantic motivational groups of nicknames, we have revealed 10 names formed from the name or surname of a husband or the street name of the husband’s family. There are 21 nicknames of UPA fighters among the anthroponyms of this group. The origin of them is not clear from the novel plot.